Mães com filhos diagnosticados com transtorno do espectro autista: análise de ansiedade, depressão e estresse - Devaliere, Marciele Ana (Universidade do Vale do Rio dos Sinos, 2017)
The present dissertation analyzes the difficulties faced by the mothers of autistic children, specifically the aspects related to anxiety, depression and stress in face of the impact of this diagnosis and the challenges that follow. The paper is composed of two articles, the first one is a review of the literature and the second is an empirical study with a qualitative approach. The first study aimed to understand the family difficulties with the child with ASD and to identify interventions that are offered to this population. The second study analyzed indicators of maternal anxiety, depression and stress and the impact of the diagnosis in the mothers of children with ASD. Four mothers with children with ASD between 3 and 6 years old, with diagnoses included as moderate and severe, participated in the study. The information was obtained by means of individual interview and application of questionnaires. These mothers belong to an institution that serves autistic children, in the interior of the state of Rio Grande do Sul, chosen for convenience. It is hoped that the results found may contribute to the care provided to these mothers.
Keywords: Autismo; Transtorno do espectro autista; Mães; Ansiedade; Depressão; Estresse; Autism; Autism spectrum disorder; Mothers; Anxiety; Depression; Stress; ACCNPQ::Ciências Humanas::Psicologia